2015
DOI: 10.3923/rjphyto.2015.188.194
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Curcumin in Ethanolic Extract of Curcuma longa Linn. and Curcuma xanthorriza Roxb. Using High Performance Liquid Chromatography with UV-Detection

Abstract: A simple and isocratic liquid chromatographic using UV detection at wavelength of 425 nm have been validated and used for quantitative analysis of curcumin in ethanolic extract of turmeric (Curcuma longa Linn.) and Curcuma xanthorriza (Zingiberaceae), indigenous to Java region, Indonesia. The method was optimized for separation of three curcuminoids namely curcumin, demethoxycurcumin and bisdemethoxycurcumin using Waters Xterra MS C18 column (4.6×250 mm, 5 μm). The mobile phase used consisted of aquabidestilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…While turmeric from Southeast Asia contained curcuminoids more than 1,800 mg/100 g dry weight. Nugroho, Rohman, Lukitaningsih, Rakhmawati, and Sudjadi () reported that curcumin in turmeric from Indonesia is in the range of 3.03%–7.31%. This variation of the content of active phytochemicals was caused by several factors such as environmental factors of each growing location (Kumar, Yadav, Yadav, & Yadav, ; Liu, Liu, Yin, & Zhao, ; Liu et al, ; Ncube, Finnie, & Van Staden, ; Rapinski, Liu, Saleem, Arnason, & Cuerrier, ; Stanković, Ćurčić, Zlatić, & Bojović, ), plant development stage (Omezzine, Daami‐Remadi, Ladhari, & Haouala, ), planting period (Brasileiro, Leite, Casali, Pizziolo, & Coelho, ), and harvesting period (Brasileiro et al, ; Watson, Wright, McBurney, Taylor, & Linforth, ).…”
Section: Resultsmentioning
confidence: 99%
“…While turmeric from Southeast Asia contained curcuminoids more than 1,800 mg/100 g dry weight. Nugroho, Rohman, Lukitaningsih, Rakhmawati, and Sudjadi () reported that curcumin in turmeric from Indonesia is in the range of 3.03%–7.31%. This variation of the content of active phytochemicals was caused by several factors such as environmental factors of each growing location (Kumar, Yadav, Yadav, & Yadav, ; Liu, Liu, Yin, & Zhao, ; Liu et al, ; Ncube, Finnie, & Van Staden, ; Rapinski, Liu, Saleem, Arnason, & Cuerrier, ; Stanković, Ćurčić, Zlatić, & Bojović, ), plant development stage (Omezzine, Daami‐Remadi, Ladhari, & Haouala, ), planting period (Brasileiro, Leite, Casali, Pizziolo, & Coelho, ), and harvesting period (Brasileiro et al, ; Watson, Wright, McBurney, Taylor, & Linforth, ).…”
Section: Resultsmentioning
confidence: 99%
“…The UV-vis detector was monitored at 244 nm and the injection volume for all samples and standards was 40 μL. quantitative HPLC analysis of each compound was calculated according to its peakarea [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…One unit of SOD is defined as the amount of SOD enzyme needed to produce 50% dismutation of superoxide radicals (Erujawa et al, 2010). This assay (Nugroho et al, 2015) in Curcuma species and xanthorrhizol in Curcuma xanthorrhiza (Ramdani et al, 2016 The levels of glutathione (GSH), glutathione reductase (GR), glutathione peroxidases (GPO), and glutathione S-transferase (GST) are frequently used as in vivo antioxidant measures. GSH, an intra-cellular reductant involved in oxidation-reduction processes resulting in the formation of glutathione disulfide (GSSG), has been known to play an important role in metabolism, catalysis, and transport.…”
Section: Evaluation Of In Vivo Antioxidant Activitiesmentioning
confidence: 99%
“…The rhizomes of Curcuma species is a source of the yellow dye and historically has been exploited as spices and food preservatives, flavoring agent, and remedy for the treatment of many diseases due to chemical compounds contained (Rajkumari et al, 2017). The main components which are believed to be responsible for several biological activities of Curcuma species including antioxidants are curcuminoid (Nugroho et al, 2015), a group of phenolics compounds of curcumin, demethoxycurcumin and bisdemethoxycurcumin ( Figure 1). In this review, the antioxidant activities in vivo of C. longa and C. xanthorrhiza were highlighted.…”
Section: Introductionmentioning
confidence: 99%